Ovarian ablation in early breast cancer: overview of the randomised trials - Early Breast Cancer Trialists' Collaborative Group (Elsevier, 1996)
Background Among women with early breast cancer, the effects of ovarian ablation on recurrence and death have been assessed by several randomised trials that now have long follow-up. In this report, the Early Breast Cancer Trialists' Collaborative Group present their third 5-yearly systematic overview (meta-analysis), now with 15 years' follow-up.